PatryTer Political-Academic Project - Latin American and Caribbean Journal of Geography and Humanities - Costa, Everaldo Batista da (2018)
The PatryTer spelling brings the Bolivarian sense of the Patria Grande as a continental unit and territorial integration, which are distinguished by the form and content of the cities, the countryside and the hegemonic domination of “nature” in Latin America and the Caribbean. Cities, countryside and “nature” (as geographic referents) have re-signified a number of popular and global heritages [the urban and the rural - specific to the region - are our greatest heritage, when the mass of the population lives and reproduces its lives in the peripheries of cities and the countryside]. In short, the idea represented in the PatryTer spelling is not restricted to the debate relative to continental heritages that the name of the magazine immediately induces. More than that, it wishes to encourage regional-continental-international discussion on geographic referents: city, countryside and socialized nature, in totalization, since they are in permanent processes of spatial intervention